PENGARUH KEPEMIMPINAN, MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (Studi Pada Pt. Industri Jamu Dan Farmasi Sido Muncul Tbk) - Radha Eva Lestari Ningrum, 13.05.51.0047; Abdul Rozak, Hasan (Students Journal of Economic and Management, 2018)
This study aims to determine the influence of leadership, motivation and work environment on employee performance PT. Industri Jamu and Farmasi Sido Muncul Tbk Semarang. Sampling technique from this research is using Accidental Sampling which amounts to 100 people. Data collection by using questionnaire (questionnaire) by way of spread list of statement to respondent to get information. The purpose of the study formulated to determine the influence of leadership, motivation and work environment on employee performance. Data were collected using factor analysis to test the validity of item statement, Crombach Alpha formula to test instrument reliability, regression analysis to test the magnitude of partial influence of each independent variable tested by regression analysis. The results of the study are: (1) leadership has a positive and significant influence on employee performance. (2) motivation has a positive and significant influence on employee performance. (3) the working environment has a positive and significant effect on employee performance.Keywords: Leadership, Work Motivation, Work Environment.